Kaposi’s sarcoma: a 15-year retrospective study in a Portuguese hospital - Leme,Hugo J. (2025)
Abstract Objectives: To characterize the demographic and clinical aspects and describe the therapeutic approaches used in patients with Kaposi’s sarcoma at Hospital Garcia de Orta. Methods: A retrospective, descriptive, and observational study that included patients with a histological diagnosis of Kaposi’s sarcoma at Hospital Garcia de Orta between March 2009 and March 2024. Results: A total of 55 patients were included, 43 males and 12 females, with an average age at diagnosis of 63.55 years. The majority of patients (67.3%) had lesions in a single anatomical location, mainly in the lower limbs. The most frequently observed subtype was classic (38.2%), followed by epidemic (36.4%), endemic (23.6%) and, finally, iatrogenic (1.8%). The time from symptom onset to diagnosis was longer in the endemic subtype (40.78 months). The epidemic subtype had the highest proportion of patients with systemic involvement (55%). The majority of patients (56.4%) underwent monotherapy. There was heterogeneity in the therapeutic modalities used. Conclusion: This study highlights there is still a considerable delay in diagnosis, underlines the evolving demographic characteristics of the disease, and emphasizes the importance of adapting treatment to the subtype and extent of the disease.